A Study on the Adhesion in the Interfacial Transition Zone Between Glass Fibre Reinforced Rebar and the Cement Matrix. Issue 3 (November 2021) - Yakovlev, Grigory; Saidova, Zarina; Drochytka, Rostislav; Gordina, Anastasiya; Pudov, Igor; Kuzmina, Natalia; Begunova, Ekaterina; Elrefai, Ali Elsaed Mohamed Mohamed
Abstract: This study is aimed at increasing the adhesion of the fibre-reinforced polymer rods to the binder in the cement-based composites in order to eliminate the problem of rod slippage under loading and broaden the application of composite reinforcement in the construction industry. It is assumed that the better adhesion of reinforcement rod to the cement matrix can be provided by increasing the cement stone structural density, and, in particular, by compacting the structure of the hydration products formed on the surface the fibre-reinforced polymer reinforcement rod. Such increase in strength and density can be achieved by adding nanodispersed additives such as metakaolin, the dispersion of carbon black and Peneco Nano Stachema primer into the composition of the cement matrix. Additional adhesion of the cement matrix to the reinforcement is ensured by coating it with the primer, which seals the structure of the cement matrix located in the interfacial transition zone between the reinforcing bar and the cement stone. Experimental study proved that the proposed approach allows the formation of a strong and dense structure in the interfacial transition zone between the cement matrix and the fibre-reinforced polymer reinforcement rod surface. The introduction of metakaolin and a dispersion of technical soot led to an increase in the adhesion strength of fibre-reinforced polymer rod with a cement matrix by 27% and 29%, respectively. The IR spectral analysis and DTA analysis results showed that the mineralogy and morphology of the hydration products was changed due to the addition of the modifying additives, thus improving the adhesion characteristics and corrosion resistance of fibre- reinforced polymer in the cement-based composites.